2014
DOI: 10.3389/fnhum.2014.00292
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral functional imaging using near-infrared spectroscopy during repeated performances of motor rehabilitation tasks tested on healthy subjects

Abstract: To investigate the relationship between the frontal and sensorimotor cortices and motor learning, hemodynamic responses were recorded from the frontal and sensorimotor cortices using functional near infrared spectroscopy (NIRS) while healthy subjects performed motor learning tasks used in rehabilitation medicine. Whole-head NIRS recordings indicated that response latencies in the anterior dorsomedial prefrontal cortex (aDMPFC) were shorter than in other frontal and parietal areas. Furthermore, the increment ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 82 publications
(115 reference statements)
3
41
0
Order By: Relevance
“…Several recent experiments paired tDCS with neuroimaging techniques such as functional near-infrared spectroscopy (fNIRS; Ishikuro, et al, 2014; Jones, Gozenman, et al, 2015; Khan, et al, 2013; McKendrick, Parasuraman, & Ayaz, 2015; Merzagora, et al, 2010; Muthalib, Besson, Rothwell, Ward, & Perrey, 2016; Muthalib, Kan, Nosaka, & Perrey, 2013), or functional magnetic resonance imaging (fMRI; Alon, Roys, Gullapalli, & Greenspan, 2011; Antal, Polania, Schmidt-Samoa, Dechent, & Paulus, 2011; Holland, et al, 2011; Kwon & Jang, 2011) to investigate neural changes after tDCS. These data lead to the interpretation that tDCS improves the efficiency of task relevant neural networks.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Several recent experiments paired tDCS with neuroimaging techniques such as functional near-infrared spectroscopy (fNIRS; Ishikuro, et al, 2014; Jones, Gozenman, et al, 2015; Khan, et al, 2013; McKendrick, Parasuraman, & Ayaz, 2015; Merzagora, et al, 2010; Muthalib, Besson, Rothwell, Ward, & Perrey, 2016; Muthalib, Kan, Nosaka, & Perrey, 2013), or functional magnetic resonance imaging (fMRI; Alon, Roys, Gullapalli, & Greenspan, 2011; Antal, Polania, Schmidt-Samoa, Dechent, & Paulus, 2011; Holland, et al, 2011; Kwon & Jang, 2011) to investigate neural changes after tDCS. These data lead to the interpretation that tDCS improves the efficiency of task relevant neural networks.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Because of the advantages of fNIRS, as described above, many previous studies have conducted motor learning experiments with fNIRS measurement and have reported learning-related cerebral activity in sensorimotor and prefrontal cortices [3]- [8]. However, few studies have considered the influences of scalp artifacts [8]. To our knowledge, this is the first study to examine such influences on the broad measurement of motor learning activity using multiple channels.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, our results showed a reasonable spatial pattern of activity and hemoglobin profiles, supporting effective removal of the scalp artifact by our method. Because of the advantages of fNIRS, as described above, many previous studies have conducted motor learning experiments with fNIRS measurement and have reported learning-related cerebral activity in sensorimotor and prefrontal cortices [3]- [8]. However, few studies have considered the influences of scalp artifacts [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hoey et al (Hoey et al, 2010), for example, a vision-based system for automated handwashing assistance monitored the psychological state of a person with dementia to adapt accordingly. An alternative, indirect estimate of activity can be obtained by monitoring brain activity through EEG or Nearinfrared spectroscopy (Ishikuro et al, 2014).…”
Section: Co-adaptation In Tasks Involving Human Motor-learning Skillsmentioning
confidence: 99%